HUBUNGAN KELENGKAPAN RESUME MEDIS DENGAN KEAKURATAN KODE DIAGNOSA KASUS PERSALINAN DI RUMAH SAKIT PANTI WALUYA SAWAHAN MALANG - Arief Setiyoargo; Romaden Marbun; Richard One Maxelly (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
The quality of hospital services is determined by improving clinical quality and customer satisfaction-oriented services. This can be seen from the completeness of filling out the medical record. One indicator of the completeness of medical records in the quantitative analysis of medical records is the completeness of the medical resume. According to the Professional Standards for Medical Recorders and Health Information, one of the competencies that must be possessed by a medical recorder is clinical classification skills, codification of diseases and other health problems and clinical procedures. The quality of disease statistical data is largely determined by the accuracy of the diagnostic code generated by a medical recorder. It is known that the inaccuracy of the diagnosis code for childbirth cases is 57% because the coder does not provide a secondary code as a form of additional information regarding the type of birth that occurred. This study used secondary data obtained from medical records of accident patients at Panti Waluya Sawahan Hospital Malang in 2021. The research design was cross sectional with a correlation study. The sample was 44 medical record files. Data analysis using Spearman Rank analysis. The results showed that there was a significant relationship between the completeness of the medical resume and the accuracy of the diagnostic code for labor cases. If a medical resume is complete, the diagnostic code for delivery cases will also be more accurate. ABSTRAKMutu pelayanan rumah sakit ditentukan dari peningkatan mutu klinis dan pelayanan yang berorientasi kepada kepuasan pelanggan. Hal tersebut dapat diketahui dari kelengkapan pengisian rekam medis. Salah satu indikator kelengkapan rekam medis dalam analisa kuantitatif rekam medis yaitu adalah kelengkapan resume medis. Standar Profesi Perekam Medis dan Informasi Kesehatan disebutkan salah satu kompetensi yang harus dimiliki oleh seorang perekam medis adalah keterampilan klasifikasi klinis, kodefikasi penyakit dan masalah kesehatan lainnya serta prosedur klinis. Mutu data statistik penyakit sangat ditentukan oleh keakuratan kode diagnosa yang dibuat oleh seorang perekam medis. Diketahui ketidakakuratan kode diagnosa kasus persalinan sebesar 57% karena disebabkan coder tidak memberikan kode sekunder sebagai bentuk keterangan tambahan terkait jenis kelahiran yang terjadi. Penelitian ini menggunakan data sekunder yang diperoleh dari rekam medis pasien kasus kecelakaan di RS Panti Waluya Sawahan Malang tahun 2021. Desain penelitian adalah cross sectional dengan studi korelasi. Sampel berjumlah 44 berkas rekam medis. Analisis data menggunakan analisis Rank Spearman. Hasil penelitian menunjukkan terdapat hubungan yang signifikan antara variabel kelengkapan resume medis dengan keakuratan kode diagnosa kasus persalinan. Jika suatu resume medis tersebut lengkap maka kode diagnosa kasus persalinan yang dihasilkan juga semakin akurat.Kata kunci: resume medis; coder; persalinan